Estudio bovinométrico y relaciones entre medidas corporales y el peso vivo en la raza Lucerna (2002)
ABSTRACT: The Present study evaluate the bovinometry measurements withers height, chest girth and body length of Lucerna animals and analysed the correlations of these with the body weight through of eight mathematical models, using 1221 females and 52 males of different ages. The body weight has increased in the cows through out the years; the withers height and the chest girth have remained stable. While the body length has increased in the breeders, the body weight and chest girth have decreased. The females‘s growth was very fast until three years old, slow between three and seven years old and stable after seven years old. The withers height had the best correlation with the body weight in all the evaluated groups and used models. Quadratic model had the best adjust in each group of females and the Gamma and Logarithmic models had the best adjust in the totals groups of females, males and Lucerna Breed.